Demographic changes in the Russian Siberia and the Far East in 1989-2019 - Dmochowski, Tadeusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Demographically, Siberia has been a remote and sparsely populated base of European Russia. The population of the Ural Federal District between 1989 and 2010 (within the borders of 2002) decreased by 0.45 million, Siberian Federal District by 4.90 million people and the Far Eastern Federal District by 1.65 million people. That is, the population of three federal districts decreased by 6.99 million people in just 21 years.
Keywords: Russian Siberia; Russian Far East; demography; population; Ural Federal District; Siberian Federal District; Far Eastern Federal District